The Virgin Mary Across Cultures : Devotion among Costa Rican Catholic and Finnish Orthodox Women. - Vuola, Elina. (Taylor & Francis Group, 2019)
This book examines women's relationship to the Virgin Mary in two different cultural and religious contexts and compares how these relationships have been analysed and explained on a theological and a sociological level.